2019
DOI: 10.1111/acfi.12575
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of recovery from the Black Saturday bushfire: demographic factors, behavioural characteristics and financial literacy

Abstract: We investigate the contribution of demographic factors, behavioural characteristics and financial literacy to recovery from the financial losses inflicted by the Black Saturday bushfire. Behavioural characteristics (such as overconfidence, self‐serving and loss aversion biases) in conjunction with bushfire survivors’ knowledge of financial indicators are used to determine recovery time. Data are collected through in‐depth interviews with bushfire survivors, academics and experts in natural disasters. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 74 publications
1
12
0
5
Order By: Relevance
“…Interestingly, there is growing evidence that contemporary published papers are becoming more in tune with diverse relevant recent real-world problems. 9 For example, Asbi et al (2020) examine recovery from the Black Saturday bushfires. Further, Xue et al (2019) consider financial well-being amongst elderly Australians, while Michalak and Ashkanasy (2020) investigate workplace psychopaths and other toxic employees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there is growing evidence that contemporary published papers are becoming more in tune with diverse relevant recent real-world problems. 9 For example, Asbi et al (2020) examine recovery from the Black Saturday bushfires. Further, Xue et al (2019) consider financial well-being amongst elderly Australians, while Michalak and Ashkanasy (2020) investigate workplace psychopaths and other toxic employees.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Asbi et al . (2020) examine recovery from the Black Saturday bushfires. Further, Xue et al .…”
Section: Introductionmentioning
confidence: 99%
“…The survey questionnaire design mirrored the concepts identified in the literature review. It incorporated items that had either been taken directly or adapted from previous studies on the topic of pandemics, financial crises, extreme events, financial planning, and behavioral finance (e.g., Asbi et al 2020 ; Chowk et al 2016 ; Greer et al 2000 ; Linsky 1975 ; Ramiah et al 2014 , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Galea et al ( 2008 ) find evidence for post-traumatic stress disorder following financial losses caused by natural disasters. Focusing on bushfires within Australia, Asbi et al ( 2020 ) identified significant and long-lasting effects on business premises, residential housing, livestock, and infrastructure. To prevent permanent damage to the economic system, Zhang and Zhang ( 2011 ) study the role of fiscal policy in economic recovery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent catastrophic and costly wildfires have spotlighted the need for research on wildfire risk as a financial valuation factor. While a healthy literature examines the cost of wildfires from a macroeconomic perspective (for a review, see Thomas et al 2017), the number of studies so far on the firm-value impacts of wildfires is small (Asbi et al 2020;Cleetus and Mulik 2014;Williams et al 2019). Much of this firm-level literature, moreover, relates to wildfire risk for insurance pricing purposes (CoreLogic 2019).…”
Section: Prior Literaturementioning
confidence: 99%